Different Class Reflected In Nicholas Spark's The Best Of Me Novel (1976): A Marxist Approach - Etami, Karlina Arum; , Drs phil. Dewi Candraningrum (2016)
The objectives of this study are to analyze Nicholas Spark's The Best of Me novel based on the structural elements of the novel and the different class in major and minor characters reflected in Nicholas Spark's The Best of Me based on a marxist approach. The research is qualitative research. The object of the study is The Best of Me novel by Nicholas Spark's which is published in 1976. It is analyzed by using Marxist approach. The method of collecting data are; reading the novel repeatedly, taking notes of important part in both primary and secondary data, underlying the important word, phrases and sentences which are related to the study, arranging the data into several part based on its classification, selecting the data by rejecting the irrelevant information which does not support the topic of the study, drawing the conclusion of the analysis that has already done in the former chapter and formulating its pedagogical suggestion. The results of the study show that the structural analysis of The Best of Me novel consists of character and characterization where Dawson and Amanda as the major character and the minor character is Frank Ridley, Tommy Cole, Ted Cole. The theme of The Best of Me novel is an accident relationship becomes a tragic family accident. The setting in The Best of Me novel consists of setting of place and setting of time. The plot in The Best of Me novel using complication, exposition, climax, resolution. The point of view the novel is coming from the author where he wants to have the romance novel formula down to a science. The Marxism analysis of the novel consists of, 1) the dialectical materialism consists of the thesis is a real condition of social life of the character witihin the novel especially the condition of Dawson where he lives as a poor man. The antithesis is a social live which is live in a high status. The sinthesis appears as the impact of the above thesis and antithesis. 2) The historical materialism in the best of Me novel shows that the society use the court and prison to judge give the punishment for people that guilty. The police also part of government weapon to keep the justice in society. 3) The class struggle in the Best of Me novel shows that there are class conflict between the lower class and high class. 4) The alienation in the Best of Me novel appears where there is some certain amazing misery hapened in Dawson's life. 5) The Resolution is a way to get equal right and position in all aspect of life in society.